2016
DOI: 10.1111/gcbb.12384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agricultural Production Systems Simulator as yield predictor of Panicum virgatum and Miscanthus x giganteus in several US environments

Abstract: TITLE Evaluation of Agricultural Production Systems Simulator (APSIM) as yield predictor of Panicum virgatum and Miscanthus x giganteus in several US environments RUNNING TITLE APSIM simulating perennial bioenergy crops ABSTRACT Simulation models for perennial energy crops such as switchgrass (Panicum virgatum L.) and Miscanthus (Miscanthus x giganteus) can be useful tools to design management strategies for biomass productivity improvement in US environments. The Agricultural Production Systems Simulator (APS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 65 publications
1
27
1
1
Order By: Relevance
“…A switchgrass yield of 10 t ha −1 or higher can provide a stable supply of switchgrass for cellulosic biofuels from Indiana farmers. Evidence has shown that yields of switchgrass can be as high as 10.7 t ha −1 in Indiana . Higher yields of switchgrass also require lower land area conversion from cropland or marginal land.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A switchgrass yield of 10 t ha −1 or higher can provide a stable supply of switchgrass for cellulosic biofuels from Indiana farmers. Evidence has shown that yields of switchgrass can be as high as 10.7 t ha −1 in Indiana . Higher yields of switchgrass also require lower land area conversion from cropland or marginal land.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that yields of switchgrass can be as high as 10.7 t ha −1 in Indiana. 45 Higher yields of switchgrass also require lower land area conversion from cropland or marginal land. Reducing the variable operating cost of cellulosic biofuel production enables biorefineries to pay higher prices for feedstock and enhances the willingness of farmers to adopt switchgrass.…”
Section: Viability Of Cellulosic Biofuel Commercialization In Indianamentioning
confidence: 99%
“…where S i is the simulated value, O i is the observed value, and O is the mean of the observations. The Lin's concordance correlation coefficient (CCC) integrates precision using Pearson's correlation coefficient-which represents the proportion of the total variance in the observed data that can be explained by the model, and accuracy with bias-which indicates how far the regression line deviates from the concordance line [72]. The CCC ranges from −1 to 1, with a perfect agreement at 1.…”
Section: Functional Analysismentioning
confidence: 99%
“…The performance of the Yield-SAFE model was evaluated visually, by comparing the simulated tree and crop yields with measured ones, as well as by determining the normalized root-mean-square error (NRMSE), the coefficient of determination (R 2 ), the concordance correlation coefficient (CCC) [37], which measured the agreement between the simulated and measured yields, and the bias function of the simulated yields (SB). Statistical analysis was performed using the R software (version 3.4.2, R Core Team 2017; R Foundation for Statistical Computing, Vienna, Austria) independently for determining the NRMSE, R 2 , and SB, and using the package "epiR" [38] for calculating the CCC.…”
Section: Calibration and Validation Of The Yield-safe Model (Yield Esmentioning
confidence: 99%